RANCANGAN DRAFT STANDAR OPERASIONAL PROSEDUR (SOP) GEMPA BUMI BAGI PERSONEL AERONAUTICAL COMMUNICATION OFFICER (ACO) DI GEDUNG TOWER PERUM LPPNPI UNIT TAMBOLAKA - Nindya Prapitasari; Didi Hariyanto; Ramining Puspitaningsih (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Based on the International Civil Aviation Organization (ICAO) Doc. 9137- AN/898 Part 7 Airport Services Manual and Annex 14 Volume 1 Chapter 9.1 regarding the priority of managing safety factors which require airport and air traffic service providers to have and implement a systematic and appropriate Aerodrome Emergency Planning to ensure that the flight service system meet the appropriate level of safety. This final project describes the absence of an earthquake Standard Operating Procedure (SOP) for Aeronautical Communication Officer (ACO) personnel in the Perum LPPNPI tower building, Tambolaka Unit and the lack of complete facilities that support personnel safety which can increase the risk of casualties in the event of an earthquake. Therefore, it is necessary to immediately draw up a draft Standard Operating Procedure (SOP) for earthquakes and complete the existing safety support facilities. In the Standard Operating Procedures (SOP) for earthquakes, there are procedures that must be carried out both before, during, and after an earthquake. This study uses an applied research/tool development methodology. The results of this study are the draft Standard Operating Procedures (SOP) for earthquakes for Aeronautical Communication Officer (ACO) personnel in the tower building of Perum LPPNPI Unit Tambolaka.